1973
DOI: 10.1071/bi9731201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feefing Protected Lipid on the Uptake of Precursors of Milk Fat by the Bovine Mammary Gland

Abstract: The feeding of protected lipid to lactating dairy cows resulted in a substantial increase in the proportion of fatty acid 18:2 and a decrease in fatty acids 4:0 to 16:0 in milk fat.The triglyceride fraction of arterial blood was the only major source of longchain fatty acid for milk-fat synthesis during the feeding of protected casein or protected lipid. There was a significant increase in the arterial concentration of triglyceride and in the quantity taken up by the mammary gland during the feeding of protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1
1

Year Published

1976
1976
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 8 publications
3
6
1
1
Order By: Relevance
“…The reduction in plasma concentration of βHBA as a result of oilseed supplementation might help to explain the lower plasma concentrations of short-chain fatty acids for ewes fed oilseed-supplemented diets relative to those fed CT (Table 5). Our results are in agreement with those of Gooden and Lascelles (1973), who found that feeding protected fat to dairy cows had no effect on mammary gland uptake of glucose and βHBA.…”
Section: Plasma Metabolitessupporting
confidence: 83%
“…The reduction in plasma concentration of βHBA as a result of oilseed supplementation might help to explain the lower plasma concentrations of short-chain fatty acids for ewes fed oilseed-supplemented diets relative to those fed CT (Table 5). Our results are in agreement with those of Gooden and Lascelles (1973), who found that feeding protected fat to dairy cows had no effect on mammary gland uptake of glucose and βHBA.…”
Section: Plasma Metabolitessupporting
confidence: 83%
“…Although the present investigations showed that there were no dietary effects on the overall concentrations of the major plasma lipids at higher intakes of tallow and polyunsaturated fatty acid containing diets, increased concentrations of ruminant plasma lipids have been observed (21,(39)(40)(41). As a result of feeding diet B in the present experiment, the concentration of triglycerides within the VLDL fraction was considerably increased and there was a compensatory decrease in the proportion of cholesteryl esters.…”
Section: Discussioncontrasting
confidence: 70%
“…Thus, in the ruminant animal, it is generally accepted (42.43) that the provision of long chain fatty acids for milk fat production occurs predominantly through the triglycerides contained within the lipoproteins of density less than 1.006. Furthermore, it has been shown that the changes in the 18:2 concentrations within the milk fat which occurred as a result of feeding a "protected" PUFA diet could be accounted for specifically by the changes produced in the concentration and 18:2 content elicited within the triglycerides of the VLDL and chylomicron classes (39). Conversely, the failure of an unprotected PUFA diet to produce any effect on milk fat composition has in turn been associated with an inability to influence, for any length of time, the 18:2 concentration of this plasma lipoprotein fraction.…”
Section: Discussionmentioning
confidence: 99%
“…About half of the fatty acids, restricted to the long chain fatty acids, are derived from blood plasma lipids of dietary origin and to a lesser extent from mobilisation of body lipid stores3132. This explains why milk fat composition can be highly variable depending on the diet and the nutritional status3334. Because all cows in this study shared the same genetic background and were farmed together, the observed differences in the fatty acid composition must have been generated by de novo fat synthesis in the mammary gland.…”
Section: Discussionmentioning
confidence: 94%